Reasons for unsuccessful research submissions to JAAPA. - Reed, Harrison M PA-C; Dehn, Richard W. MPA, PA-C, DFAAPA; Bushardt, Reamer L. PharmD, PA-C, DFAAPA (JAAPA: Journal of the American Academy of Physician Assistants (Lippincott Williams & Wilkins), 2022)
Objective: PA authors face many barriers to publication and may benefit from additional transparency in the editorial decision-making process. This study examined the most common reasons for rejection of original research submissions to JAAPA. Methods: Senior JAAPA editors conducted a thematic analysis of reviewer and editor comments and used these broad themes to classify the reasons for rejection of original research manuscripts submitted to JAAPA. Results: From October 2015 through December 2018, 77 research manuscripts were submitted to JAAPA. Fifty-six manuscripts were rejected, resulting in an overall rejection rate of 73.7%. Common reasons for rejection included: methodologic issues (55.4%), content outside the journal's scope (42.9%), poor writing quality (17.9%), guideline nonadherence (3.6%), lack of novelty (3.6%), and author(s) declining to revise the manuscript (1.8%). Conclusion: The most common reasons for manuscript rejection can be overcome through research planning and manuscript preparation.